Dynamic strength analysis of the key components of the beam-type pumping unit with dynamic tracking balance (Fracture and Structural Integrity, 2021)
Aiming at the shortages of large reversing impact, high energy consumption and poor balance effect of conventional beam-type pumping unit, the design scheme of beam-type pumping unit with dynamic tracking balance is proposed. The load-displacement curves from on-site trial shows that pumping with dynamic tracking balance has a better balance effect, and a production and power efficiency. According to the designed structure, the dynamic responses of the beam and connecting rods are analyzed. The results show that the maximum Mises stresses in the beam and connecting rod are 36.96 MPa and 27.83 MPa, respectively. The key components of designed beam-type pumping unit with dynamic tracking balance meet the requirement of strength.
Keywords: Dynamic tracking balance; Load balance; Power efficiency; Dynamic response; Strength